Comparative Morphophysiological Analyses and Molecular Profiling Reveal Pi-Efficient Strategies of a Traditional Rice Genotype - Mehra, Poonam; Pandey, Bipin K.; Giri, Jitender (Frontiers in Plant Science, 2016)
Phosphate (Pi) deficiency severely affects crop yield. Modern high yielding rice genotypes are sensitive to Pi deficiency whereas traditional rice genotypes are naturally compatible with low Pi ecosystems. However, the underlying molecular mechanisms for low Pi tolerance in traditional genotypes remain largely elusive. To delineate the molecular mechanisms for low Pi tolerance, two contrasting rice genotypes, Dular (low Pi tolerant) and PB1 (low Pi sensitive), have been selected. Comparative morphophysiological, global transcriptome and lipidome analyses of root and shoot tissues of both genotypes grown under Pi deficient and sufficient conditions revealed potential low Pi tolerance mechanisms of the traditional genotype. Most of the genes associated with enhanced internal Pi utilization (phospholipid remobilization) and modulation of root system architecture (RSA) were highly induced in the traditional rice genotype, Dular. Higher reserves of phospholipids and greater accumulation of galactolipids under low Pi in Dular indicated it has more efficient Pi utilization. Furthermore, Dular also maintained greater root growth than PB1 under low Pi, resulting in larger root surface area due to increased lateral root density and root hair length. Genes involved in enhanced low Pi tolerance of the traditional genotype can be exploited to improve the low Pi tolerance of modern high yielding rice cultivars.